Strengthening Mini Cake Micro-Enterprises Through Digital Marketing, Digitalization, and Business Website Optimization - Della Olivia Caterina Kalangit; Rusliansyah Rusliansyah; Armini Ningsih (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2026)
This community service program aims to enhance the digital marketing capacity of a mini-cake micro-enterprise in Samarinda through the development and optimization of a dedicated business website. The program adopts an Asset-Based Community Development (ABCD) approach, emphasizing the utilization of existing business assets, including product quality, customer networks, and basic digital capabilities. The target beneficiaries are the owner and employees of the mini-cake micro-enterprise. The activities were implemented over a three-month period through asset mapping, participatory planning, website development, hands-on training, and mentoring. The main outcomes include a functional business website, a standardized digital product catalogue, and improved website management skills. Program evaluation using pre- and post-training assessments, observations, and participant feedback indicated a notable improvement in digital literacy and operational readiness. In conclusion, the program demonstrates that the ABCD-based approach effectively supports sustainable digital marketing adoption and can be replicated for similar micro-enterprises.